2020
DOI: 10.2147/ndt.s221540
|View full text |Cite
|
Sign up to set email alerts
|

<p>Spotlight on Compulsive Sexual Behavior Disorder: A Systematic Review of Research on Women</p>

Abstract: Purpose of Review: World Health Organization recently included compulsive sexual behavior disorder (CSBD) to the upcoming 11th edition of International Classification of Diseases (6C72). Despite the potential benefits of this decision (eg, the acceleration of research in the field will allow the development of effective treatments), previous research focused mainly on men, and as a result, we do not have an accurate clinical picture of compulsive sexual behavior (CSB) among women. Therefore, in this systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 176 publications
(329 reference statements)
4
43
0
Order By: Relevance
“…Since women in Japan may mainly use comics as pornographic material (Mori, 2017), differences in the content of pornographic material may have contributed to the gender differences observed in the results of the present study. In addition, a recent review focused on women with compulsive sexual behavior indicated that severe compulsive sexual behavior and urges to engage in pornography use are lower among women than men (Kowalewska et al, 2020). However, there is a possibility of problematic use among women, as some women reported using pornography with impaired control in the present study.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Since women in Japan may mainly use comics as pornographic material (Mori, 2017), differences in the content of pornographic material may have contributed to the gender differences observed in the results of the present study. In addition, a recent review focused on women with compulsive sexual behavior indicated that severe compulsive sexual behavior and urges to engage in pornography use are lower among women than men (Kowalewska et al, 2020). However, there is a possibility of problematic use among women, as some women reported using pornography with impaired control in the present study.…”
Section: Discussionmentioning
confidence: 48%
“…However, there is a possibility of problematic use among women, as some women reported using pornography with impaired control in the present study. Given the general dearth of research on female pornography use (Kraus et al, 2016b;Kowalewska et al, 2020), there is a need for increased focus on this issue in the Japanese context, as well as on types of sexual content that women use in particular, and women's patterns of sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There are many important issues that should be taken into account in future research. The current conceptualization of CSBD is based on studies involving mostly heterosexual men, thus, we do not know the prevalence estimates, clinical patterns of sexual functioning, as well as neurobiological mechanisms of the groups such as women or sexual minorities (70). Due to the lack of scientific exploration, we cannot apply available criteria to individuals from these omitted groups.…”
Section: Future Directionsmentioning
confidence: 99%
“…Gender differences are also common in behavioral addictions. For example, research indicates that boys are exposed to pornography at earlier age than girls, consume more pornography and tend more often to self-define themselves as addicted to pornography (see [ 81 , 82 ] for a recent reviews). In addition, boys have higher attentional bias toward sexual cues and tend to have higher prevalence of CSBD (e.g., [ 5 , 29 , 83 ].…”
Section: Introductionmentioning
confidence: 99%